Rapid identification of Bacillus anthracis by cell wall and capsule components direct fluorescent antibody assay - Lily Natalia; Rahmat Setya Adji (Indonesian Center for Animal Research and Development (ICARD), 2008)
During the outbreak of anthrax, early diagnosis is critical for effective treatment. Numerous attempts have been made to design antigen based detection tests and to rapidly identify truly anthrax specific antigens for B. anthracis. In Indonesia, standard identification of B. anthracis relies on a combination of time consuming steps including bacterial culture and Ascoli precipitin test, which can take several days to provide a diagnosis. In this study, two component (cell wall and capsule) direct fluorescent antibody assay (DFA) were developed to rapidly identify and to directly detect capsulated B. anthracis. The component used in cell wall DFA (CW-DFA) assay is polysaccharide-peptidoglycan complex, which was prepared from B. anthracis culture by cell lysis, guanidine and sodium dodecyl sulphate (SDS) extraction. The component used in capsule DFA (CAP-DFA) is poly-D-glutamic acid (PGA) which were prepared by extraction of B. anthracis capsule. Component of polysaccharide-peptidoglycan complex and PGA conjugated with hemocyanin were then used as immunogen for immunizing rabbits using Freund’s complete/incomplete adjuvant. The hyperimmune sera were then collected, purified and conjugated to Fluorecent Iso Thiocyanate (FITC). B. anthracis isolates and non B. anthracis isolates were tested by the CW-DFA and CAP-DFA Assays. B. cereus, B. subtilis, other Bacillus sp. and other Gram positive rod bacteria were negative, while capsulated B anthracis gave positive results. The two component (CW DFA and CAP-DFA) assay are specific rapid confirmatory test for capsulated B. anthracis. Key Words: Bacillus anthracis, Cell Wall and Capsule Direct Fluorescent Antibody Assay